Extended‐release guanfacine hydrochloride in 6–17‐year olds with ADHD: a randomised‐withdrawal maintenance of efficacy study. (12th February 2016) - Newcorn, Jeffrey H.; Harpin, Valerie; Huss, Michael; Lyne, Andrew; Sikirica, Vanja; Johnson, Mats; Ramos‐Quiroga, Josep Antoni; van Stralen, Judy; Dutray, Benoit; Sreckovic, Sasha; Bloomfield, Ralph; Robertson, Brigitte
Abstract : Background: Extended‐release guanfacine hydrochloride (GXR), a selective α2A‐adrenergic agonist, is a nonstimulant medication for attention‐deficit/hyperactivity disorder (ADHD). This phase 3, double‐blind, placebo‐controlled, randomised‐withdrawal study evaluated the long‐term maintenance of GXR efficacy in children/adolescents with ADHD. Methods: Children/adolescents (6–17 years) with ADHD received open‐label GXR (1–7 mg/day). After 13 weeks, responders were randomised to GXR or placebo in the 26‐week, double‐blind, randomised‐withdrawal phase (RWP). The primary endpoint was the percentage of treatment failure (≥50% increase in ADHD Rating Scale version IV total score and ≥2‐point increase in Clinical Global Impression‐Severity compared with RWP baseline, at two consecutive visits). The key secondary endpoint was time to treatment failure (TTF). Trial registration: ClinicalTrials.gov identifier NCT01081145; EudraCT 2009‐018161‐12. Results: A total of 528 participants enrolled; 316 (59.8%) entered the RWP. Treatment failure occurred in 49.3% of the GXR and 64.9% of the placebo group ( p  =   0.006). TTF was significantly longer in GXR versus placebo ( p  =   0.003). GXR was well tolerated. Conclusions: Guanfacine hydrochloride demonstrated long‐term maintenance of efficacy compared with placebo in children/adolescents with ADHD. Implications of the placebo substitution design and findings with different ADHD medications are discussed. Abstract : Phase 3, double‐blind, placebo‐controlled, randomized‐withdrawal study evaluating the long‐term maintenance of GXR efficacy in children/adolescents with ADHD.